Factors Of Raising A Spiritually Mature Generation - Qiyam Nazarov (Global Scientific Publishing, 2024)
The article analyzes topical issues related to the upbringing of the spiritually developed young generation and the role of humanitarian education in this process.
Keywords: education and upbringing; quality education; humanitarian education